Ethnopharmacological survey of Samburu district, Kenya - Kaburia Humphrey F; Koros Kipsengeret B; Wagate Cyrus G; Lanyasunya Adamson L; Mbaria James M; Nanyingi Mark O; Munenge Rahab W; Ogara William O (BMC, 2008)
Abstract Background Ethnobotanical pharmacopoeia is confidently used in disease intervention and there is need for documentation and preservation of traditional medical knowledge to bolster the discovery of novel drugs. The objective of the present study was to document the indigenous medicinal plant utilization, management and their extinction threats in Samburu District, Kenya. Methods Field research was conducted in six divisions of Samburu District in Kenya. We randomly sampled 100 consented interviewees stratified by age, gender, occupation and level of education. We collected plant use data through semi-structured questionnaires; transect walks, oral interviews and focus groups discussions. Voucher specimens of all cited botanic species were collected and deposited at University of Nairobi's botany herbarium. Results Data on plant use from the informants yielded 990 citations on 56 medicinal plant species, which are used to treat 54 different animal and human diseases including; malaria, digestive disorders, respiratory syndromes and ectoparasites. Conclusion The ethnomedicinal use of plant species was documented in the study area for treatment of both human and veterinary diseases. The local population has high ethnobotanical knowledge and has adopted sound management conservation practices. The major threatening factors reported were anthropogenic and natural. Ethnomedical documentation and sustainable plant utilization can support drug discovery efforts in developing countries.